Superalloys 2008 (Eleventh International Symposium) 2008
DOI: 10.7449/2008/superalloys_2008_565_572
|View full text |Cite
|
Sign up to set email alerts
|

Mean vs. Life-Limiting Fatigue Behavior of a Nickel Based Superalloy

Abstract: The mean and the life-limiting behavior under fatigue of the nickel-based superalloy, IN100, separated (or converged) as a function of stress level and dwell loading. This behavior was related to the control of the life-limiting behavior by the smallcrack growth regime, producing its much slower response to stress level and dwell-time, relative to the mean-lifetime behavior. The lifetime probability density is therefore, modeled as a superposition of the crack growth lifetime density and a meanlifetime density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 10 publications
1
38
0
Order By: Relevance
“…2. This separation in fatigue lifetimes, known as bimodal or competing-modes fatigue, has been observed in a wide range of alloys, including the superalloys: Rene'95 [21,22], Rene'88DT [23], IN100 [8,[24][25][26][27][28][29], Waspaloy [30], the single crystal alloy PWA 1484 [31], the titanium alloys Ti-10-2-3 [23,[32][33][34], Ti-6Al-2Sn-4Zr-6Mo [35][36][37][38][39][40][41][42], Ti-6Al-4V [43][44][45][46][47], gamma titanium aluminides [48,49], the aluminum alloy 7075-T651 [50], and others. Although such a separation of fatigue response has been known for some time [51], the significance of this behavior has not yet been generally captured in the strategies for fatigue design of turbine engine materials.…”
Section: Life Limits and Competing-mode Of Fatiguementioning
confidence: 99%
See 1 more Smart Citation
“…2. This separation in fatigue lifetimes, known as bimodal or competing-modes fatigue, has been observed in a wide range of alloys, including the superalloys: Rene'95 [21,22], Rene'88DT [23], IN100 [8,[24][25][26][27][28][29], Waspaloy [30], the single crystal alloy PWA 1484 [31], the titanium alloys Ti-10-2-3 [23,[32][33][34], Ti-6Al-2Sn-4Zr-6Mo [35][36][37][38][39][40][41][42], Ti-6Al-4V [43][44][45][46][47], gamma titanium aluminides [48,49], the aluminum alloy 7075-T651 [50], and others. Although such a separation of fatigue response has been known for some time [51], the significance of this behavior has not yet been generally captured in the strategies for fatigue design of turbine engine materials.…”
Section: Life Limits and Competing-mode Of Fatiguementioning
confidence: 99%
“…As noted earlier, we previously established a general computational framework for physics-based understanding of fatigue variability [24,40]. In this approach, the lifetime distribution was modeled as a superposition of the probability densities of the crack-growth-dominated lifetime (Type I) and the crack-initiation-dominated, mean lifetime (Type II).…”
Section: Modeling Bimodal Fatiguementioning
confidence: 99%
“…In Ti-6-2-4-6, this has been attributed to a superposition of the crack-growth-controlled (life-limiting) mechanism with the crack-initiationdominated (mean) behavior [27]. The effect of microstructural and extrinsic variables on the lifetime variability can then be modeled in terms of the distinct influence of these on the crack initiation and growth regimes, affecting the degree of separation between the two superimposing behaviors, as shown in [27][28][29]. In terms of the crack-initiation mechanism, in the RS-free condition (i.e., electropolished surface), failures occurred exclusively by surface-initiation, as indicated in Fig.…”
Section: Fatigue Variability Behavior In the Rs-free Conditionmentioning
confidence: 99%
“…However, this aspect has not been sufficiently addressed in past SP studies. In the RS-free condition, for instance, it has been demonstrated that the average microstructure or the distribution about the mean characteristics is not an accurate predictor of the lifetime variability [27,28]. In particular, the lower-tail of lifetime has been shown to be often controlled by an extreme microstructural configuration or arrangement, which otherwise has a small probability of occurrence, and may not be accounted for in conventional statistical characterization of microstructure [29].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays the maximum stress of the aero-engine turbine disk is approximately 1100 Mpa [5] (with the rotation speed 10000r/min). And considering the existing test data [6,7] , the stress levels were set at 1100MPa and 1200MPa for the low cycle fatigue and 900MPa and 1000MPa for the high cycle fatigue respectively.…”
Section: Experiments Proceduresmentioning
confidence: 99%